2021
DOI: 10.3389/fphar.2021.576448
|View full text |Cite
|
Sign up to set email alerts
|

A Journey From SARS-CoV-2 to COVID-19 and Beyond: A Comprehensive Insight of Epidemiology, Diagnosis, Pathogenesis, and Overview of the Progress into Its Therapeutic Management

Abstract: The 2019 novel coronavirus (2019-nCoV), commonly known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or coronavirus disease 2019 (COVID-19), was first revealed in late 2019 in Wuhan city, Hubei province, China. It was subsequently spread globally and thereby declared as a pandemic by WHO in March 2020. The disease causes severe acute respiratory illness and is highly contagious due to the fast-onward transmission. As of the mid of November 2020, the disease has affected 220 countries with mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 211 publications
(308 reference statements)
0
8
0
1
Order By: Relevance
“…SARS-CoV-2 causes a potentially severe respiratory illness with mortality seen in 1%–10% ( Meyerowitz-Katz and Merone, 2020 ; Shoaib et al, 2021 ) of the aged population ( O'Driscoll et al, 2021 ). Several compounds that either modulate the human immune response or have anti-inflammatory effects have been evaluated in clinical trials, among which Paxlovid was recently approved by the FDA as an oral anti-viral treatment against SARS-CoV-2 ( Sanders et al, 2020 ; Mahase and Kmietowicz, 2021 ; Yousefi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 causes a potentially severe respiratory illness with mortality seen in 1%–10% ( Meyerowitz-Katz and Merone, 2020 ; Shoaib et al, 2021 ) of the aged population ( O'Driscoll et al, 2021 ). Several compounds that either modulate the human immune response or have anti-inflammatory effects have been evaluated in clinical trials, among which Paxlovid was recently approved by the FDA as an oral anti-viral treatment against SARS-CoV-2 ( Sanders et al, 2020 ; Mahase and Kmietowicz, 2021 ; Yousefi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we observed some clinically instructive results by MR analysis. Elevated levels of CRP and IL-10 were commonly happened in severe COVID-19 patients [ 33 ], and IBD patients were at higher risk of developing severity [ 34 ]; in contrast, vasodilator use and vitamin D supplements might reduce the risk of COVID-19 infections and mortality [ 35 , 36 ]. These clinical observations were consistent with their causal associations with ARDS development, which may guide the ARDS care management, especially during COVID-19 severe progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that gender differences in susceptibility toward SARS-CoV-2 may be associated with the immune response (26). The data of 10 European countries on the distribution of SARS-COV-2 cases by gender showed that women of working age outnumbered infected men (27). Interestingly, it is reported that male sex is one of the major risk factors for severe SARS-CoV-2 disease (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%